2021
DOI: 10.3390/ijms22179385
|View full text |Cite
|
Sign up to set email alerts
|

circBTBD7 Promotes Immature Porcine Sertoli Cell Growth through Modulating miR-24-3p/MAPK7 Axis to Inactivate p38 MAPK Signaling Pathway

Abstract: Sertoli cells are the crucial coordinators to guarantee normal spermatogenesis and male fertility. Although circular RNAs (circRNAs) exhibit developmental-stage-specific expression in porcine testicular tissues and have been thought of as potential regulatory molecules in spermatogenesis, their functions and mechanisms of action remain largely unknown, especially in domestic animals. A novel circBTBD7 was identified from immature porcine Sertoli cells using reverse transcription PCR, Sanger sequencing, and flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Compared with wild-type cells, the differentially expressed genes in the FOXCUT knockdown cells are shown in Figure 4 C. Finally, p38 , BCL2L11 , ZNF395 , STX6 , and RAB5B were confirmed as candidate genes [Figure 4 D]. However, based on the existing research, [ 40 , 41 ] further research led to the choice of p38 as the target. Collectively, we constructed a mutant p38 plasmid according to the ligation site for further study [Figure 4 E].…”
Section: Resultsmentioning
confidence: 99%
“…Compared with wild-type cells, the differentially expressed genes in the FOXCUT knockdown cells are shown in Figure 4 C. Finally, p38 , BCL2L11 , ZNF395 , STX6 , and RAB5B were confirmed as candidate genes [Figure 4 D]. However, based on the existing research, [ 40 , 41 ] further research led to the choice of p38 as the target. Collectively, we constructed a mutant p38 plasmid according to the ligation site for further study [Figure 4 E].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, miR-24-3p serves as a regulatory factor of Smad5, which exerts important functions on osteogenic di erentiation [58]. Also, evidence demonstrated that the overexpression of miR-24-3p upregulated the phosphorylation activity of MAPK14 [59].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, circLMO7 increased the ratio of bovine myoblasts cells in the S-phase of the cell cycle and protected them from apoptosis by binding to miR-378a-3p [ 33 ]. Additionally, circBTBD7 activates the p38 MAPK signaling pathway by regulating the miR-24-3p/MAPK7 axis, promoting proliferation and inhibiting apoptosis in immature porcine sertoli cells [ 34 ]. In this study, circ0001470 facilitated EECs proliferation and cell cycle, and the knockdown of circ0001470 induced EECs apoptosis.…”
Section: Discussionmentioning
confidence: 99%